ANALISIS KATA GANTI BAHASA BATAK DIALEK BATAK TOBA KELURAHAN KLAMANA DISTRIK SORONG TIMUR KOTA SORONG - Soulisa, Irwan; Naibaho, Erlycha C.; Gifelem, Agustinus G. (LPPM Politeknik Saint Paul Sorong, 2025)
Formulation of the problem How is the use of pronouns in the Batak language, Batak Toba dialect in the Klamana sub-district, East Sorong district, Sorong city? The purpose of the study To find out what are the uses of pronouns in the Batak language, Batak Toba dialect in the Klamana sub-district, East Sorong district, Sorong city. This study is in the form of qualitative descriptive. The method used is the descriptive method. Data sources for the Batak language, Toba dialect and from the internet. Data collection techniques using data collection can be done by interview, questionnaire, observation, and a combination of the three, through 1) Free Listening Technique, Participation, 2) Interview Technique, 3) Note-taking Technique, 4) Tapping technique, 5). The data analysis techniques used include data reduction, data presentation and drawing conclusions or verification. The conclusion is the First person pronoun consisting of 4 first person singular pronouns. The Second person pronoun consisting of 4 second person pronouns. The Third person pronoun consisting of 4 third person pronouns